2012
DOI: 10.1103/physreve.85.041132
|View full text |Cite
|
Sign up to set email alerts
|

Weakening interaction suppresses spontaneous symmetry breaking in two-channel asymmetric exclusion processes

Abstract: This paper has studied spontaneous symmetry breaking (SSB) phenomenon in two types of two-channel asymmetric simple exclusion processes (ASEPs). One common feature of the two systems is that interactions for each species of particle happen at only one site, and the system reduces to two independent ASEPs when interaction vanishes. It is shown that with the weakening of interaction, the SSB is suppressed. More interestingly, the SSB disappears before the interaction is eliminated. Our work thus indicates that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The SSB can also be observed in a system in which the interactions for each species of particle happen at only one site in the two-channel TASEP with two species of particles. [38] It is shown that with the weakening of interaction, the SSB is suppressed. Authors in Ref.…”
Section: Spontaneous Symmetry Breakingmentioning
confidence: 99%
See 2 more Smart Citations
“…The SSB can also be observed in a system in which the interactions for each species of particle happen at only one site in the two-channel TASEP with two species of particles. [38] It is shown that with the weakening of interaction, the SSB is suppressed. Authors in Ref.…”
Section: Spontaneous Symmetry Breakingmentioning
confidence: 99%
“…Authors in Ref. [38] reported an interesting phenomenon that the SSB disappears before the interaction is eliminated. However, the reason has not been given in Ref.…”
Section: Spontaneous Symmetry Breakingmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles move along the lattice obeying a hard-core exclusion principle. This simple model can reproduce many non-equilibrium phenomena such as spontaneous symmetry breaking, [30][31][32][33][34][35][36][37][38][39][40][41][42] boundary-induced [43][44][45] and bulk-induced [46] phase transitions, phase separation and condensation, [47][48][49][50][51] shock formation, [11,12,46,52] and so on. Thus, as Blythe and Evans [4] pointed out, "our interest in the ASEP lies in its having acquired the status of a fundamental model of nonequilibrium statistical physics in its own right in much the same way that the Ising model has become a paradigm for equilibrium critical phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] From then on, the phenomenon in ASEP models has gained a great deal of attention. [32][33][34][35][36][37][38][39][40][41][42] However, the mechanism of this phenomenon is still not well understood.…”
Section: Introductionmentioning
confidence: 99%